Jan Szczepan Otrębski – lituanista dwóch uniwersytetów w Wilnie i w Poznaniu - Gawrońska-Garstka, Magdalena (Scripta Neophilologica Posnaniensia, 2018)
Jan Szczepan Otrębski – lituanista dwóch uniwersytetów w Wilnie i w Poznaniu